Mindfulness-Based Therapy dalam Penanganan Depresi Remaja: Literature Review - Kusumawardani, Paramitha Amelia; Pungzup, Saowaros; Rinata, Evi; Maryam, Effy Wardati; Soekarno, Krisjayanti; Agmar, Alfisyar (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: to explore the effectiveness of mindfulness-based therapy in reducing depressive symptoms among adolescents through a literature review. Methods: This article used a descriptive qualitative design with a literature review method, analyzing 12 scientific articles published between 2018 and 2023 that met inclusion criteria. Data were collected from EBSCO, ProQuest, PubMed, and Google Scholar database and analyzed using a thematic approach. Results: From a total of 84 articles found in the initial search, a screening process was carried out based on titles, abstracts, and the availability of full text. After going through the selection process, 30 articles were studied in depth, and a total of 12 articles met all the inclusion criteria for adolescents aged 10-19 years as the main participants and were published within the period 2018-2023. Articles that do not meet the criteria, such as editorials, opinions, non-scientific reviews, and studies that do not explicitly list MBT outcomes or interventions, are excluded from the final analysis. The results of the synthesis show that Mindfulness-Based Therapy (MBT) consistently has a positive impact in reducing symptoms of depression in adolescents Conclusion: MBT is a promising and adaptive intervention for holistically addressing adolescent depression. Integrating MBT into school programs and community-based counseling is recommended as a preventive and promotive mental health strategy.